Greening Global Trade: Strategies for Aligning with SDGs and Climate Action (Maharaja Surajmal Institute Law Journal, 2025)
Confronted with compounding crises encompassing climate change, biological diversity decline, and environmental contamination, there is an increasingly pressing imperative for the establishment of a sustainable global economy, a notion gaining prominence within the international political discourse. Simultaneously, a profound equity dilemma prevails, characterized by the exacerbation of acute socio-economic disparities both among nations and within them, coupled with marked disparities in susceptibility to ecological hazards. The COVID-19 pandemic underscored the interconnected nature of these concerns, prompting appeals to institute a recovery framework characterized by sustainability and fairness. This vision of recovery, advo cating for ecological and egalitarian principles, has garnered support from a spectrum of political ideologies and regions across the globe. The intersection of global trade policies with the SDGs and climate action presents a critical confrontation and an unparalleled scope for policymakers, businesses, and society at large. This arti cle explores the multifaceted landscape of trade policies, sustainability, and climateaction, shedding light on harmonizing these realms for a more sustainable future. We delve into the fundamental challenges existing trade policies pose that may inad vertently hinder progress toward SDGs and climate action targets. These hurdles encompass issues such as trade barriers, regulatory misalignments, and economic interests that may clash with sustainability objectives. Recognizing these obstacles is essential in order to navigate the path forward. The article also focuses on the oppor tunities and strategies available to green global trade. We explore innovative tools and mechanisms that can be harnessed to promote green trade, such as eco-labelling, green supply chains, and carbon pricing. These strategies facilitate alignment with the SDGs and climate action and create new avenues for market growth and compet itiveness.
Keywords: Climate Crisis; Green global trade; Sustain- ability; SDGs; Climate Action.